Skin blood flowmotion response to insulin iontophoresis in normal subjects - Rossi, M.; Maurizio, S.; Carpi, A. (Microvascular research, 2005)
In order to explore the mechanisms directly involved in the insulin vasodilatory activity, we studied skin blood flowmotion by means of spectral analysis of the skin forearm laser Doppler (LD) signal registered before and after iontophoresis of insulin in saline (I.S.) (0.1 ml Humulin R 100 IU/ml diluted 1/10 in 0.9% saline) or pure saline (P.S.) (0.1 ml of 0.9% saline) in twenty normal subjects. Skin LD blood perfusion was also measured in conventional perfusion unit (PU; 1 PU = 10 mV). Using a Fast Fourier transform algorithm, power density (PD) of the total flowmotion spectrum, from 0.009 to 1.6 Hz, was measured in PU/Hz. Power density of five skin flowmotion frequency intervals (F.I.) within 0.009–0.02 Hz, 0.02–0.06 Hz, 0.06–0.2 Hz, 0.2–0.6 Hz and 0.6–1.6 Hz (referred to endothelial, sympathetic, myogenic, respiratory and heart activity, respectively) was also measured in PU/Hz. The mean skin LD perfusion increment (expressed as percent change from baseline) was significantly higher after I.S. than after P.S. ( P < 0.001, ANOVA for repeated measures). Skin flowmotion total spectrum mean PD value significantly increased following iontophoresis of both P.S. (from 1.06 ± 0.62 to 1.86 ± 0.94 PU/Hz, P < 0.005) and I.S. (from 1.07 ± 0.92 to 2.39 ± 1.73 PU/Hz P < 0.00005), however, the mean PD increment was significantly higher after I.S. than after P.S. (1.27 ± 0.98 PU/Hz versus 0.69 ± 0.67 PU/Hz, P < 0.05). Only the flowmotion component referred to myogenic activity showed a percent PD increase from baseline significantly higher in response to I.S. than to P.S. iontophoresis (114.5 ± 21.8% versus 58.8 ± 17.9%, respectively, P < 0.05). These findings show that insulin has a vasodilatory activity on skin microvascular district. The higher increase of total blood flowmotion PD and particularly of the component related to the myogenic activity in response to insulin iontophoresis suggests that the cutaneous vasodilatory activity of insulin is, in part, related to an important action of this hormone on skin microvascular smooth muscle.